Pengaruh Penghargaan Finansial, Pertimbangan Pasar Kerja, Lingkungan Kerja Dan Pelatihan Profesional Terhadap Minat Mahasiswa Akuntansi Universitas Buana Perjuangan Karawang Menjadi Akuntan Publik - Mia Melati; Devi Astriani; Fista Apriani Sujaya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Public accountants have an important role in improving the quality and quality of information in the financial sector. On the other hand, students' choice of profession as public accountants is still quite low, with quite strict job regulations and lengthy procedures, making some students reluctant to pursue this profession. Evaluating and analyzing the effect of financial rewards, labor market considerations, work environment and professional training on the interest of accounting students at Buana Perjuangan Karawang University to become public accountants is the aim of this research. As a research tool used multiple linear regression analysis method. Accounting students were used as the population, as well as the purposive sampling method used to determine the sample. Utilizing the help of SPSS version 26 as an analysis tool. The results of the partial hypothesis test show that there is a positive and significant influence on the factors of financial rewards, labor market considerations, and professional training on the interest of accounting students to become public accountants. However, the work environment variable has no significant effect on the interest of accounting students to become public accountants. Meanwhile, simultaneously (simultaneously) on financial rewards, labor market considerations, work environment and professional training there is a positive and significant influence on the interest of accounting students to become public accountants. Keywords: Financial Rewards, Labor Market, Work Environment, Professional Training